Disseminated Intravascular Coagulation in Cancer: An Update - Levi, Marcel (Seminars in thrombosis and hemostasis, 2019)
Cancer often leads to the activation of coagulation, manifesting as disseminated intravascular coagulation (DIC) in its most extreme form. DIC is characterized by systemic intravascular coagulation activation (leading to deposition of intravascular platelets and fibrin) and simultaneous consumption of coagulation proteins and thrombocytes (which may cause bleeding complications). The clinical course of DIC in patients with malignancies is typically less intense compared with DIC complicating alternative clinical settings, including systemic inflammatory responses following infection or traumatic injury. A more slowly proceeding, less fulminant, and widespread hemostatic derangement can remain asymptomatic. Eventually, the ongoing consumption may result in low levels of platelets and coagulation factors, and bleeding complications (frequently localized at the site of the tumor or distant metastases) may be the first clinical manifestation of DIC. An alternative clinical scenario is dominated by thrombotic complications, ranging from clinically manifest vascular thrombosis to microvascular platelet plugs. The main principle of DIC management is adequate treatment of the precipitating disorder; however, there are clinical presentations that may require additional supportive strategies specifically aimed at the amelioration of the coagulopathy.